Antipodean Social Policy Responses to Economic Crises. (7th October 2013) - Starke, Peter
Abstract In this article, I analyze the social policy reactions to economic crises in Australia and New Zealand. After the financial crisis of 2008, Australia built its crisis management strategy around a large fiscal stimulus with a significant social policy component, whereas New Zealand did not. While the government enacted fiscal stimulus measures, the social policy component was small and the government soon returned to welfare retrenchment and workfare policy. Based on a detailed account of recent crisis policies as well as a condensed overview of previous crisis responses (to the 1970s oil shocks, the early 1990s recession and the Asian financial crisis), I discuss the contribution of a number of factors to explaining this difference between Australia and New Zealand. These factors include: idiosyncratic causes such as the Australian mining boom and the Christchurch earthquakes, partisan politics, interest group structures, political institutions and policy legacies. The analysis shows that the recent differences cannot fully be explained through idiosyncratic factors, as partisan ideology was already crucial in strategic policy decisions during the first months of the crisis. The historical pattern further supports this conclusion.